Unemployment Insurance in the United States : Analysis of Policy Issues; Topics in Unemployment Insurance Financing - Morel, Sylvie (Relations industrielles / Industrial Relations, 2000)
The article reviews the books, "Unemployment Insurance in the United States : Analysis of Policy Issues," edited by by Christopher J. O'Leary and Stephen A. Wandner, and "Topics in Unemployment Insurance Financing" by Wayne Vroman.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Finance; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unemployment insurance